2017
DOI: 10.2320/matertrans.m2016439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Carbonate on Phase Transformation of High-Magnesium Laterite Ore

Abstract: The phase transformation of high-magnesium laterite ore were investigated during the reduction roasting process. In the absence of sodium carbonate [Na 2 CO 3 ], the X-ray diffraction results indicate that the [Fe Ni] alloy existed in ore in the form of taenite. The taenite particles is ne and the size is approximately 30-40 nm, which indicate that the nickel and iron are not migrated and aggregated during the non-smelting reduction roasting process. In the presence of sodium carbonate, the intensity of [Fe Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Both MFC and CMC show typical peaks of cellulose structure at 22.6 and 15.6°, while the sharp peaks at 31.8 and 45.5°in the CMC spectrum correspond to inorganic content constituting the sodium salts. 36,37 The sharp prominent peak of the 002 plane, characteristic of pure MFC, is found to be notably influenced by functionalization. Small molecules (CMC and β-alanine) are found to elicit no obvious shifts in the peaks; therefore, they present only small changes in the crystal structure.…”
Section: S(t)emmentioning
confidence: 98%
See 1 more Smart Citation
“…Both MFC and CMC show typical peaks of cellulose structure at 22.6 and 15.6°, while the sharp peaks at 31.8 and 45.5°in the CMC spectrum correspond to inorganic content constituting the sodium salts. 36,37 The sharp prominent peak of the 002 plane, characteristic of pure MFC, is found to be notably influenced by functionalization. Small molecules (CMC and β-alanine) are found to elicit no obvious shifts in the peaks; therefore, they present only small changes in the crystal structure.…”
Section: S(t)emmentioning
confidence: 98%
“…The characteristic peaks and crystallinity index of nanocellulose and functionalized nanocellulose.Both MFC and CMC show typical peaks of cellulose structure at 22.6⁰ and 15.6⁰ while the sharp peaks at 31.8⁰ and 45.5⁰ in the CMC spectrum correspond to inorganic content constituting the sodium salts36,37 . The sharp prominent peak of the 002 plane, characteristic of pure MFC, is found to be notably influenced by functionalization.…”
mentioning
confidence: 99%
“…With a further increase in the temperature, to 700°C, the mineral phase of the nickel laterite ore changed significantly, and the amorphous magnesium silicate recrystallized to form a forsterite phase (Mg 2 SiO 4 ) and enstatite phase (MgSiO 3 ). 21) The formation of the forsterite phase results in a decrease in the metallization rate of nickel. As the temperature increased, the nickel-iron nuclei continued to grow, while the peaks of ¡-Fe and Awaruite[FeNi 3 ] gradually increased because of the presence of greater quantities of metal iron.…”
Section: Characterization Of the Samplesmentioning
confidence: 99%
“…Morphology has a great impact on the performance of materials in the period of catalysis. In past several decades, Bi metal with various morphologies, such as nanotubes, nanowires, nanocubes, nanoparticles, triangular nanoplates, nanospheres and hollow nanospheres have been successfully synthesized . Recently, Fan and co‐workers reported that bismuth hollow nanospheres are efficient in Cr (VI) adsorption .…”
Section: Introductionmentioning
confidence: 99%